Bearding the Capability Deprivation Machine: The Pedagogical Deal for Post-apartheid Young South Africa - Soudien, Crain (Critical Studies in Teaching and Learning, 2023)
The purpose of this essay is to reflect on how we in South Africa are managing the task of higher education in an environment marked by poverty. The paper makes the argument that the question of how to proceed when considering the relationship between the phenomenon of poverty and the experience of education is regularly resolved through invoking the syllogism that increased levels of education will bring about increased levels of income. Drawing on Sen and his ideas of capability deprivation, it is contended here that income-deprivation ideas by themselves do not adequately encompass the full complexity of how deprivation works. The approach taken here, therefore, is different. It works with the proposition that education needs to respond to the full range of social, cultural and other inhibiting factors with respect to the development of capabilities. Positing, therefore, the contention that human beings need to flourish in all the areas of their social lives and not just the space of work, the paper argues for the need to develop an education system that works with capabilities that are valuable in the full range of social spaces young South Africans inhabit. Using this introduction as a point of departure, the paper begins with an attempt at characterising the phenomenon of poverty and then moves on to look at the challenges the sector faces in teaching and learning with respect to it. Thereafter it provides an overview of the sector's responses to these challenges and finally, drawing on the idea of capability deprivation, makes a critical assessment of these responses.